2020
DOI: 10.1177/1049909120951129
|View full text |Cite
|
Sign up to set email alerts
|

Early Use of the Palliative Approach to Improve Patient Outcomes in HIV Disease: Insights and Findings From the Care and Support Access (CASA) Study 2013-2019

Abstract: Young men of color who have sex with men (yMSM) living with human immunodeficiency virus (HIV) in syndemic environments have been difficult-to-retain in care resulting in their being at-risk for poor health outcomes despite availability of effective once-daily antiretroviral treatment (ART). Multiple methods have been implemented to improve outcomes for this cohort; none with sustainable results. Outpatient HIV staff themselves may be a contributing factor. We introduced multidisciplinary staff to the concept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…From my point of view that level of education might affect the size of their information because scientific level JNSBU increased, the bulk of knowledge must be increased to serve the study because they were able to understand tool of study. This result was in contrast with Alexander et al, (2021), who studied "Early Use of the Palliative Approach to Improve Patient Outcomes in HIV Disease: Insights and Findings From the Care and Support, USA" and found that, the majority of participants were 18-30 years of age with Mean ±SD (29. ±3.9), Forty-five percent were employed.…”
Section: Resultsmentioning
confidence: 60%
“…From my point of view that level of education might affect the size of their information because scientific level JNSBU increased, the bulk of knowledge must be increased to serve the study because they were able to understand tool of study. This result was in contrast with Alexander et al, (2021), who studied "Early Use of the Palliative Approach to Improve Patient Outcomes in HIV Disease: Insights and Findings From the Care and Support, USA" and found that, the majority of participants were 18-30 years of age with Mean ±SD (29. ±3.9), Forty-five percent were employed.…”
Section: Resultsmentioning
confidence: 60%
“…38,[41][42][43]46,50 Many of the experiences captured in the literature were characterized by fear and worry largely associated with a pervasive culture of discrimination and stigma, the heteronormative and cisnormative assumptions of health workers, being on the receiving end of homophobic and transphobic behaviors, social isolation which worsened in the context of aging, losing autonomy, or being trans, and concerns about confronting an undignified death. [38][39][40][41][42][43][44][45][47][48][49][50] The preferences of LGBTQ+ individuals pertained to the inclusion of chosen families in decision-making and care planning, disclosure of their sexual orientation and/or gender if clinical environments were perceived as safe, and a strong desire to maintain functional independence and agency. [41][42][43][48][49][50] Many study participants reported either anticipated or actual bias, discrimination, or mistreatment from healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies described LGBTQ+ identities within samples using different parameters. Two papers recruited men who have sex with men, 39,45 seven recruited LGB, LGBT, or LGBTI samples, 38,40-42,44,46,50, four papers focused on African American/Black…”
Section: Study Populationsmentioning
confidence: 99%
See 2 more Smart Citations